IMPLEMENTASI PENDIDIKAN INKLUSI DI SDN 13 BANAWA: TANTANGAN DAN STRATEGI - Muliati Mursak; Asep Supena; Totok Bintoro; Ikhwan Abduh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Inclusive education serves as a means for special needs students to receive equal learning opportunities alongside their peers in regular schools. This study aims to: 1) Identify the primary challenges faced by SDN 13 Banawa in implementing inclusive education, and 2) Analyze the strategies employed by the school to address these challenges. This qualitative research employs a case study approach, with data collected through observation, interviews, and documentation. The study, conducted in October 2024, involved three subjects: one school principal, one teacher, and one parent of a student. The data analysis techniques included data preparation, coding, and interpretation of research findings to draw conclusions. The results reveal five key challenges: 1) low teacher competence, 2) lack of specialized instructors for special needs students, 3) absence of dedicated funding, 4) the non-implementation of a special curriculum for special needs students, and 5) inadequate learning facilities. To overcome these challenges, the school has implemented several strategies, including: 1) self-guided training through the Merdeka Mengajar Platform (PMM) to enhance teacher competence in inclusive education, 2) utilization of the independent curriculum, 3) collaboration with parents, and 4) leveraging BOS (School Operational Assistance) funds for financing. The findings suggest that these strategies are short-term solutions and may encounter challenges in the long term. Future research is recommended to explore more sustainable strategies and assess the long-term impacts of the measures undertaken by schools.